2014
DOI: 10.1016/j.jbiosc.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of anaerobic sulfur-oxidizing microbial communities in up-flow anaerobic sludge blanket reactor treating municipal sewage

Abstract: A novel wastewater treatment system consisting of an up-flow anaerobic sludge blanket (UASB) reactor and a down-flow hanging sponge (DHS) reactor with sulfur-redox reaction was developed for treatment of municipal sewage under low-temperature conditions. In the UASB reactor, a novel phenomenon of anaerobic sulfur oxidation occurred in the absence of oxygen, nitrite and nitrate as electron acceptors. The microorganisms involved in anaerobic sulfur oxidation have not been elucidated. Therefore, in this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…The number of representatives of the phyla Caldiserica and Chloroflexi was markedly lower, whereas that of the phylum Proteobacteria was only slightly higher than those in the earlier period. A previous study ( 1 ) showed that the uncultured bacteria of phylum Caldiserica were the main bacterial group observed in the UASB reactor, which was consistent with the results observed in this study. However, in the initial and second anaerobic sulfur oxidation periods, the number of representatives of the phylum Caldiserica decreased.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The number of representatives of the phyla Caldiserica and Chloroflexi was markedly lower, whereas that of the phylum Proteobacteria was only slightly higher than those in the earlier period. A previous study ( 1 ) showed that the uncultured bacteria of phylum Caldiserica were the main bacterial group observed in the UASB reactor, which was consistent with the results observed in this study. However, in the initial and second anaerobic sulfur oxidation periods, the number of representatives of the phylum Caldiserica decreased.…”
Section: Resultssupporting
confidence: 93%
“…These consortia, which mediate AOM with sulfate, were composed of anaerobic methanotrophic (ANME) archaea and SRB ( 24 ). Although ANME-related archaea were not detected in the UASB reactor, methanogenic archaea and SRB were detected, as reported previously by Aida et al ( 1 ). This finding suggested that SRB that were present in the UASB reactor acted as the main players in anaerobic sulfur oxidation.…”
Section: Resultssupporting
confidence: 84%
“…Several bacteria associated with Fe reduction were identified, such as Acidithiobacillus , Ferrimicrobium , and Nitrospira ( Figure 1B ). In parallel, S reduction generates energy in anaerobic environments ( Aida et al, 2014 ); and it is crucial in structuring microbial community. It could be ratified by relative high abundance of Desulfobulbus and presence of Desulfovibrio as well as Desulfococcus , Desulforhabdus , and Desulfovirga in the samples ( Figure 1C ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Thiobacillus can remove N from sediment by denitrification [74]. Additionally, Aida et al [75] showed that the genus Smithella was possibly able to aid in the sulfur oxidation in up-flow anaerobic sludge blanket reactors. In this study, the operation of SMFC probably supported S 2− oxidation at the anode.…”
Section: Changes In Microbial Communities In Smfcsmentioning
confidence: 99%